Chinese Herbal Preparation SaiLuoTong Alleviates Brain Ischemia via Nrf2 Antioxidation Pathway–Dependent Cerebral Microvascular Protection - Fan, Xiao-Di; Yao, Ming-Jiang; Yang, Bin; Han, Xiao; Zhang, Ye-Hao; Wang, Guang-Rui; Li, Peng; Xu, Li; Liu, Jian-Xun (Frontiers in Pharmacology, 2021)
Stroke is one of the most devastating diseases worldwide. Chinese herbal preparation SaiLuoTong capsule (SLT) showed outstanding therapeutic effects on stroke and its sequelae. This study is to further elucidate its therapeutic mechanism. We duplicated a permanent cerebral ischemia model in rats by MCAO, and used SLT (33 and 16.5 mg/kg) to intervene. The results showed SLT dose-dependently decreased infarction volumes, relieved neuron degenerations and loss, and ameliorated neurological functions, and the dose of 33 mg/kg had statistical significances (compared with the model group, p<0.05); SLT of 33 mg/kg also significantly inhibited the elevation in brain water content and the loss in claudin-1 and occludin expressions; additionally it significantly increased nucleus translocation of Nrf2, elevated expression of HO-1, and raised activity of SOD and content of GSH (compared with the model group, p<0.05 or 0.01). These results testified SLT’s anti-stroke effect, and hint this effect may be related to the protection on cerebral blood vascular endothelial cells (CBVEC) that is dependent on Nrf2 pathway. To further testify, we cultured hCMEC/D3 cells, duplicated OGD/R model to simulate ischemia, and used SLT (3.125, 6.25, and 12.5 mg/L) to treat. SLT dose-dependently and significantly inhibited the drop in cell viabilities, and activated Nrf2 pathway as facilitating Nrf2 nucleus translocation, and increasing HO-1 expression, SOD activity and GSH content (compared with the model group, p<0.05 or 0.01); lastly, the anti-OGD/R effects of SLT, including raising cell viabilities, inhibiting the elevation in dextran permeability, and preserving expressions of claudin-1 and occludin, were all abolished by Nrf2 siRNA interference. The in vitro experiment undoubtedly confirmed the direct protective effect of SLT on CBVEC and the obligatory role of Nrf2 pathway in it. Collectively, data of this study suggest that SLT’s therapeutic effect on brain ischemia is related to its Nrf2 dependent CBVEC protection.